HIV Tat excites D1 receptor-like expressing neurons from rat nucleus accumbens. (1st September 2017) - Brailoiu, G. Cristina; Deliu, Elena; Barr, Jeffrey L.; Console-Bram, Linda M.; Ciuciu, Alexandra M.; Abood, Mary E.; Unterwald, Ellen M.; Brailoiu, Eugen
Highlights: We investigated effects of HIV-1 trans-activator of transcription (Tat) on D1-expressing accumbens neurons (NAcc). Tat releases Ca 2+ from IP3 -sensitive stores, followed by TRPC & P/Q channel opening. Tat depolarizes NAcc neurons via Na + influx via TRPC and voltage-sensitive channels. Cocaine potentiates dose-dependently Tat-induced Ca 2+ responses in NAcc. We infer a mechanism of modulation of NAcc in cocaine-abusing HIV-infected patients. Abstract: Background: HIV-1 infection and drug abuse are frequently co-morbid and their association greatly increases the severity of HIV-1-induced neuropathology. While nucleus accumbens (NAcc) function is severely perturbed by drugs of abuse, little is known about how HIV-1 infection affects NAcc. Methods: We used calcium and voltage imaging to investigate the effect of HIV-1 trans-activator of transcription (Tat) on rat NAcc. Based on previous neuronal studies, we hypothesized that Tat modulates intracellular Ca 2+ homeostasis of NAcc neurons. Results: We provide evidence that Tat triggers a Ca 2+ signaling cascade in NAcc medium spiny neurons (MSN) expressing D1-like dopamine receptors leading to neuronal depolarization. Firstly, Tat induced inositol 1, 4, 5-trisphsophate (IP3 ) receptor-mediated Ca 2+ release from endoplasmic reticulum, followed by Ca 2+ and Na + influx via transient receptor potential canonical channels. The influx of cations depolarizes the membrane promoting additional Ca 2+ entry through voltage-gated P/Q-type Ca 2+ channels and opening of tetrodotoxin-sensitive Na + channels. By activating this mechanism, Tat elicits a feed-forward depolarization increasing the excitability of D1-phosphatidylinositol-linked NAcc MSN. We previously found that cocaine targets NAcc neurons directly (independent of the inhibition of dopamine transporter) only when IP3 -generating mechanisms are concomitantly initiated. When tested here, cocaine produced a dose-dependent potentiation of the effect of Tat on cytosolic Ca 2+ . Conclusion: We describe for the first time a HIV-1 Tat-triggered Ca 2+ signaling in MSN of NAcc involving TRPC and depolarization and a potentiation of the effect of Tat by cocaine, which may be relevant for the reward axis in cocaine-abusing HIV-1-positive patients.